IMPROVING GROSS MOTOR SKILLS BY GROSS KINESTHETIC-AND CONTEMPORARY-BASED PHYSICAL ACTIVITY IN EARLY CHILDHOOD - Sutapa, Panggung; Suharjana, Suharjana (LPMPP Universitas Negeri Yogyakarta, 2019)
It is often heard the differences in opinion that with a lot of physical activity will make a child stupid. This experimental study aimed to determine the effect of kinesthetic-based and contemporary physical activity on early childhood on increasing gross motor skills. Research subjects were 68 children aged 5-6 years, 28 girls and 40 boys, divided into two groups, group A was treated with kinesthetic-based physical activity and group B received contemporary treatment. The instruments used to collect data on gross motor abilities consisted of five types, namely 20 meter sprinting, arm power by throwing a tennis ball, power legs with long jump without the start, balance by walking on a long beam 4 meters, and agility with Illinois tests. The results show that kinesthetic-based physical activity and contemporary-based activities can significantly increase gross motor skills in young children and seen from the difference in the mean effectiveness of kinesthetic-based physical activities is better for improving running ability, agility and balance, while the ability to throw a ball and the ability to jump better physical activity based on contemporary.